Uwarunkowania i następstwa konkurencyjności banków spółdzielczych - Adamowicz, Mieczysław; Kołodziej, Elżbieta (Conditions and Results of Cooperative Banks Competitiveness, 2006)
Cooperative banks have a stable competitive position in rural areas. They service not only rural households but also enterprises and commune self-governments. These banks are situated near clients and their good relations with both clients and banks' owners are an important advantage over others.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 17-24